Hygiene and Sanitation Factors Affecting Contamination of Soil-Transmitted Helminths in Household Water Sources in Jember, Indonesia - Epafroditus Sanjaya Adiguna; Wiwien Sugih Utami; Ika Rahmawati Sutejo; Bagus Hermansyah; Yunita Armiyanti (Althea Medical Journal, 2022)
Background: Water sources used by households are at risk of contamination by soil-transmitted helminths (STH). Hygiene and sanitation have an essential role in the transmission and contamination of STH. The objective of this study was to analyze whether there was an association between hygiene and sanitation factors with STH contamination in household water sources in Jember Regency, East Java Province, Indonesia.